Power exhaust by SOL and pedestal radiation at ASDEX Upgrade and JET. (August 2017) - Bernert, M.; Wischmeier, M.; Huber, A.; Reimold, F.; Lipschultz, B.; Lowry, C.; Brezinsek, S.; Dux, R.; Eich, T.; Kallenbach, A.; Lebschy, A.; Maggi, C.; et al.
Highlights: Stable operation with fully detached targets in all-metal devices demonstrated Power exhaust achieved at highest heat fluxes with impurity seeding of N, Ne and Kr Radiated power fraction of up to 90% reached Radiation dominantly from inside the confined region close to the X-point Edge impurity transport and feedback of the plasma affect stability Abstract: Future fusion reactors require a safe, steady state divertor operation. A possible solution for the power exhaust challenge is the detached divertor operation in scenarios with high radiated power fractions. The radiation can be increased by seeding impurities, such as N for dominant scrape-off-layer radiation, Ne or Ar for SOL and pedestal radiation and Kr for dominant core radiation. Recent experiments on two of the all-metal tokamaks, ASDEX Upgrade (AUG) and JET, demonstrate operation with high radiated power fractions and a fully-detached divertor by N, Ne or Kr seeding with a conventional divertor in a vertical target geometry. For both devices similar observations can be made. In the scenarios with the highest radiated power fraction, the dominant radiation originates from the confined region, in the case of N and Ne seeding concentrated in a region close to the X-point. Applying these seed impurities for highly radiative scenarios impacts local plasma parameters and alters the impurity transport in the pedestal region. Thus, plasma confinement and stability can be affected. A proper understanding of the effects by these impurities is required in order to predict the applicability of such scenarios for future devices.